KEPENTINGAN INDONESIA KERJASAMA DENGAN ARGENTINA DALAM KERANGKA FEALAC (FORUM FOR EAST ASIA-LATIN AMERICA COOPERATIONS) - Khoiriyah "; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this study was to determine and explain the development of bilateral relations with Argentina Indonesia's political economy and the interests of Indonesia in cooperation with Argentina in the framework of FEALAC. This research uses descriptive method, the data obtained from library research by collecting data in the form of secondary data from the literature and then analyze the data using quantitative analysis. By using this liberalism perspective assumes that an interdependent world economy based on free trade. Results from the study show that with the cooperation between Indonesia and Argentina within the framework of FEALAC a positive impact on the improvement of bilateral relations between the two countries are influential Indonesia to increase trade volume, particularly in improving Indonesia's exports to Argentina which will also increase the value of GDP.Keywords: FEALAC, Indonesia-Argentina bilateral relations, international cooperation